CoExplorer: Generative AI Powered 2D and 3D Adaptive Interfaces to Support Intentionality in Video Meetings - Park, Gun Woo (Warren); Panda, Payod; Tankelevitch, Lev; Rintel, Sean (CHI EA 2024, 2024)
Current online meeting technologies lack holistic support for reducing the effort of planning and running meetings. We present CoExplorer2D and CoExplorerVR, generative AI (GenAI)-driven technology probes for exploring the significant transformative potential of GenAI to augment these aspects of meetings. In each system, before the meeting, these systems generate tools that allow Current online meeting technologies lack holistic support for reducing the effort of planning and running meetings. We present CoExplorer2D and CoExplorerVR, generative AI (GenAI)-driven technology probes for exploring the significant transformative potential of GenAI to augment these aspects of meetings. In each system, before the meeting, these systems generate tools that allow synthesis and ranking of attendees’ key issues for discussion, and likely phases that a meeting would require to cover these issues. During the meeting, these systems use speech recognition to generate 2D or VR window layouts with appropriate applications and files for each phase, and recognize the attendees’ progress through the meeting’s phases. We argue that these probes show the potential of GenAI to contribute to reducing the effort required for planning and running meetings, providing participants with a more engaging and effective meeting experiences.